2007
DOI: 10.1099/ijs.0.65049-0
|View full text |Cite
|
Sign up to set email alerts
|

Methermicoccus shengliensis gen. nov., sp. nov., a thermophilic, methylotrophic methanogen isolated from oil-production water, and proposal of Methermicoccaceae fam. nov.

Abstract: A thermophilic, methylotrophic methanogen, strain ZC-1T, was isolated from the Shengli oilfield, China. Cells of strain ZC-1T were motile cocci, 0.7–1.0 μm in diameter and always occurred in clusters of two to four cells. Lysis-susceptibility experiments and analysis of transmission electron micrographs of strain ZC-1T suggested the presence of a proteinaceous cell wall. Strain ZC-1T used methanol, methylamine and trimethylamine as substrates for methanogenesis. Optimal growth, with a doubling time of around 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…Based on published information on the closest relatives within the Methanomicrobiales, Methanococcales, and Methanopyrales, which consist almost exclusively of hydrogenotrophic methanogens (19Ϫ20, 35, 37Ϫ42), H 2 and/or formate is a likely energy source of 9 of 21 mcrA phylotypes detected. In addition, we detected one phylotype of the genus Methanohalophilus and three of the family Methermicoccaceae, lineages that catabolize methanol and methylamines (43,44). Aceticlastic groups (Methanosaeta, Methanosarcina, Zoige cluster I) (45Ϫ46) were not detected.…”
Section: Resultsmentioning
confidence: 95%
“…Based on published information on the closest relatives within the Methanomicrobiales, Methanococcales, and Methanopyrales, which consist almost exclusively of hydrogenotrophic methanogens (19Ϫ20, 35, 37Ϫ42), H 2 and/or formate is a likely energy source of 9 of 21 mcrA phylotypes detected. In addition, we detected one phylotype of the genus Methanohalophilus and three of the family Methermicoccaceae, lineages that catabolize methanol and methylamines (43,44). Aceticlastic groups (Methanosaeta, Methanosarcina, Zoige cluster I) (45Ϫ46) were not detected.…”
Section: Resultsmentioning
confidence: 95%
“…Genomic DNA was isolated by SDS treatment after grinding under liquid N 2 as previously described (19), and its GϩC content was determined by the thermal denaturation (T m ) method (6,32) and the high-performance liquid chromatography (HPLC) method (35). The genomic DNA of Escherichia coli K-12 was used as a reference.…”
Section: Methodsmentioning
confidence: 99%
“…Investigations of microbial communities have used 16S rRNA gene sequence analysis to characterize archaea in the deep subsurface such as in terrestrial rocks (45,52), petroleum reservoirs (8,9,18,39,40,42,58), faults (37,49,57), coal seams (11,48), gas fields (36), and subseafloor gas hydrates (17,33,35). These studies have demonstrated the abundance and diversity of methanoarchaea.…”
mentioning
confidence: 99%